2021
DOI: 10.1111/plb.13363
|View full text |Cite
|
Sign up to set email alerts
|

Proline, a multifaceted signalling molecule in plant responses to abiotic stress: understanding the physiological mechanisms

Abstract: Abiotic stresses have a detrimental impact on plant growth and productivity and are a major threat to sustainable crop production in rapidly changing environments. Proline, an important amino acid, plays an important role in maintaining the metabolism and growth of plants under abiotic stress conditions. Many insights indicate a positive relationship between proline accumulation and tolerance of plants to various abiotic stresses. Because of its metal chelator properties, it acts as a molecular chaperone, an a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

9
156
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 354 publications
(166 citation statements)
references
References 201 publications
(353 reference statements)
9
156
0
1
Order By: Relevance
“…It may be due to that Pro could maintain osmotic balance, scavenge free radicals and singlet oxygen, stimulate antioxidant enzyme activity, and maintain the stability of proteins. 49 SP had a positive correlation with antioxidant enzymes, GSH, and ASA ( P < .01). It may be due to that SP has similar components to antioxidant enzymes and GSH, and ASA could promote the synthesis of SP.…”
Section: Discussionmentioning
confidence: 92%
“…It may be due to that Pro could maintain osmotic balance, scavenge free radicals and singlet oxygen, stimulate antioxidant enzyme activity, and maintain the stability of proteins. 49 SP had a positive correlation with antioxidant enzymes, GSH, and ASA ( P < .01). It may be due to that SP has similar components to antioxidant enzymes and GSH, and ASA could promote the synthesis of SP.…”
Section: Discussionmentioning
confidence: 92%
“…Heat tolerance is acquired when, in response to the excessive production of ROS, plants initiate heat stress responsive pathways for ROS-scavenging, such as the accumulation of proline and other osmolytes. ABA, the hormone regulating stomatal aperture under heat stress, has been suggested to be responsible for the initiation of other physiological responses, such as the accumulation of proline in stressed plants [24,27]. Proline has diverse roles, such as stabilizing proteins, membranes, and subcellular structures, protecting cellular functions by scavenging ROS, and acting as a signaling molecule [23].…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, proline has additional roles, such as stabilizing proteins, membranes, and subcellular structures, protecting cellular functions by scavenging ROS, and acting as a signalling molecule [23]. Thus, proline plays an important role in maintaining the metabolism and growth of plants under abiotic stress conditions and many reports indicate a positive relationship between proline accumulation and tolerance of plants to various abiotic stresses [24].…”
Section: Introductionmentioning
confidence: 99%
“…Both salinity and low temperature induce osmotic alteration in plant cells, but salinity additionally creates ionic imbalance (i.e., excess sodium and associated potassium deficiency) [ 52 ], which could have exerted a stronger inhibition on the growth of cardoon calli than chilling. Opposite to NaCl-treated calli, the growth of chilled calli recovered after 14 days, possibly reflecting an osmotic adjustment through accumulation of osmolytes that usually keep cells turgid for growth [ 53 ]. In line with this observation, the value of lipid peroxidation revealed that chilling stress is successfully counterbalanced by the plant’s antioxidant machinery as suggested by the level of MDA that was even lower than the control.…”
Section: Discussionmentioning
confidence: 99%